Safety Protocols in Nursing: Best Practices for Documenting Nutritional Assessments and Dermatological Treatments in Laboratory Settings - Alshubromi, Ali Barjas; Darbashi, Ahmed Mohamed; Alsharari, Saad Abdullah Saud; Alzahrani , Ahmad Salem A; Alsharari, Musallam Mohammed M; Al-Mutairi, Seham Fahad; Alshaibani, Nader Nasser Nader; Almobaraki , Nawal Mohammed Saleh; Alotaibi , Salma Hulel; Awaji, Seham Mohammad Abdu; Alsaud , Kholud Mohammed; Alkaabi, Fatmah Mohammad; et al. (Journal of Ecohumanism, 2024)
Enterocutaneous fistulas (ECFs) present significant challenges in clinical management, often leading to malnutrition and increased morbidity. Effective nutritional support is crucial for patient recovery, particularly in post-surgical settings.This review systematically examines best practices for documenting nutritional assessments and dermatological treatments for patients with ECF in laboratory environments. A comprehensive literature search was conducted across multiple databases, including PubMed, MEDLINE, and Scopus, focusing on studies published from 2019 to 2023 that address nutritional management and care protocols for ECF patients.The findings highlight the importance of a multidisciplinary approach involving surgeons, nutritionists, and nursing staff in managing ECF. Nutritional assessments using standardized tools such as the ASPEN/FELANPE guidelines are essential for identifying malnutrition. The review also emphasizes the role of parenteral nutrition (PN) as a critical component of care, particularly in patients with high-output ECF, while monitoring fluid and electrolyte balance remains paramount.Implementing robust documentation practices and effective nutritional support strategies is vital for improving outcomes in patients with ECF. The integration of evidence-based guidelines into routine clinical practice can enhance interdisciplinary communication and optimize patient care.